Digital Competence of Citizens: A Growing Need in a Digitalized Society [la Competencia Digital de la Ciudadanía, Una Necesidad Creciente en Una Sociedad Digitalizada] - Silva-Quiroz, J (GTE-Educational Technology Group, University of the Balearic Islands, 2020)
The information society has generated new digital literacy which, because of its aspects and implications for education, training and the workplace, has coined the term digital competence. This articled deals with the problem of digital competence of citizens, understood as a key element for performing in the knowledge society, and putting the potential and opportunities offered by digital technology to its best use in different areas of professional and personal development of individuals. To this end, it addresses the issue of digital competence, the digital divide as an element that hinders development and proposes a set of recommendations that would facilitate the development of digital competence of citizens. © 2020 GTE-Educational Technology Group, University of the Balearic Islands. All rights reserved.